Negative Affectivity and Problematic Alcohol Use Among Latinos in Primary Care: The Role of Emotion Dysregulation. Issue 2 (2nd April 2016) - Paulus, Daniel J.; Bakhshaie, Jafar; Lemaire, Chad; Garza, Monica; Ochoa-Perez, Melissa; Valdivieso, Jeanette; Velasco, Ricardo Valdes; Bogiaizian, Daniel; Kauffman, Brooke Y.; Robles, Zuzuky; Neighbors, Clayton; Zvolensky, Michael J.
Abstract : Objective : Latinos are the largest and most rapidly growing racial/ethnic group in the United States. In Latino communities, alcohol is the most widely abused substance, yet there is little empirical understanding of the factors underlying problematic alcohol use among Latinos. The current study explored whether negative affectivity exerted an indirect effect via emotion dysregulation in relation to two alcohol-related outcomes.Methods : Participants were 316 Latinos attending a community-based primary care facility ( M age = 39.3, SD = 11.3; 85.4% female; 95.3% first language Spanish), who completed a variety of self-report and interview measures. Mediation analyses evaluated the indirect effect of negative affectivity via emotion dysregulation on problematic drinking and symptoms of alcohol dependence.Results : While there was no direct or total effect of negative affectivity on either alcohol-related outcome, negative affectivity was significantly associated with both problematic alcohol use and symptoms of dependence via emotion dysregulation. Effect sizes were in the medium range, K 2 = .09 and .10, respectively. Post-hoc multiple mediation analyses evaluated subfactors of emotion dysregulation as mediators of the negative affectivity–alcohol associations. These results suggested that difficulties engaging in goal-directed behavior might be particularly important in explaining the association between negative affectivity and problematic alcohol use/symptoms of dependence. Last, independent mediation analyses evaluated emotion dysregulation subfactors and found that limited access to effective emotion regulation strategies and difficulties engaging in goal-directed behavior were, independently, significant mediators for both outcomes. Nonacceptance of emotional responses may also mediate negative affectivity and problematic drinking. Surprisingly, impulse control difficulties was not a significant mediator in any model.Conclusions : These data provide novel insight that among Latinos in primary care, emotion dysregulation is a possible mechanism underlying the indirect relationship between negative affectivity and problematic alcohol use and symptoms of dependence. Results also highlight specific facets of emotion dysregulation as potential targets of intervention. Future research should be longitudinal in nature, be conducted among more representative samples, and utilize measures that will better assess the potential variability in these associations. Results of such work may inform the development of alcohol treatment interventions incorporating the use of adaptive emotion regulation among Latinos in primary care.